Expression of bone morphogenetic protein signaling pathway players in the jejunum and colon of adult rats - Emma Cogo; Edwin Fouché; Charline Buisson; Adenike Omotoyinbo; Fabrice Pierre; Françoise Guéraud; Pascale Plaisancié (European Journal of Histochemistry)
The bone morphogenetic protein (BMP) pathway, which plays a crucial role in the control of intestinal epithelial cell homeostasis, has been studied in mice and humans, leading to an understanding of its involvement in several intestinal pathologies. However, the expression and localization of the various actors (ligands, antagonists, receptors) of this pathway remain unknown in the rat intestine, although this species is widely used in pathophysiology studies. Here, we aimed to determine the expression and localization of the various players in the BMP pathway in the jejunum and colon of the rat using RT-qPCR and immunohistochemistry. BMP2, mainly localized in epithelial cells, was the most expressed ligand in the jejunum and colon in comparison with BMP4, BMP6 and BMP7. We showed for the first time that BMP7 was highly expressed in epithelial cells in both tissues. BMP2, BMP6 and BMP7 ligands were also present in the enteric nervous plexuses, as the BMP receptors and antagonists Noggin and Chordin-like 1. The expression of BMP antagonists and ligands in enterocytes and mature colonocytes could suggest a paracrine or autocrine feedback modulation at the cellular level. Finally, all the studied BMP actors were present in colonic vessel walls including GREM1, a BMP antagonist described as pro-angiogenic and also being a ligand for VEGFR receptors. These data provided a good correlation between the observations in rats compared to those in humans and highlighted the importance of the BMP pathway not only in the intestinal epithelium, but also in both the enteric nervous system and vascular system. Our work lays the foundations for further studies on the involvement of the BMP pathway in rat models of intestinal pathophysiology.